Trans-aortic left ventricular thrombo-embolectomy following COVID-19 infection. Issue 9 (27th September 2021) - Janula, Michael; Navarro, Andre; Bonello, John; Schembri, Kevin; Borg, Alex
Abstract: Left ventricular thrombosis is a known complication of myocardial infarction. COVID 19 has been shown to produce a procoagulant state resulting in venous and less commonly arterial thrombosis. Here, we describe a patient who presented with a non-ST elevation myocardial infarction (NSTEMI), in the context of a COVID 19 infection. This NSTEMI resulted in the formation of a large pedunculated apical thrombus, which was initially managed conservatively, however ultimately required surgical thromboembolectomy. Access to the left ventricle was gained via the transaortic route in order to avoid ventriculotomy in a patient with a reduced LV systolic function. Post-operative imaging confirmed complete resection of thrombus.